Pious yet Trendy Young Muslim: ‘The Bros Team’ and Public Qur’an in Indonesia - Imas Lu’ul Jannah (UIN Sunan Kalijaga Yogyakarta, 2022)
This article discusses the intersection of Quranic reciting practices and pop culture through the emergence of The bros team, which is popular among modern Indonesian young Muslims. Since the fall of the New Order dictatorship, the Quran's recitation has become more public, shaping the Islamic soundscape in Indonesia’s online-offline public spaces. As a group of Quran reciters representing pious Muslim youth in Indonesia, the Bros team's popularity among Indonesians youth demonstrates how young people manage their identity as part of global pop culture while being rooted to Islamic orthodoxy. This group uploads murattal content of Quranic recitations on social media such as YouTube and Instagram. Those contents highlights how they appear to recite the Quran by incorporating parts of pop culture trend that are familiar to young people. Pertaining to this facts, this research contends that mediated Quranic practice via social media platforms shapes particular implications and treatments of the Quran and performers. Through online and offline field research, this study investigates how the popularity of The Bros team articulates the religious development of young Muslims in relation to the practice of public Quran recitation as a form of negotiating identity for devout Muslim Youths in Indonesia.